A novel surgical technique of left atrial appendage closure. Issue 9 (11th July 2020) - Ram, Eilon; Orlov, Boris; Sternik, Leonid
Abstract: Background and Aims: Surgical left atrial appendage occlusion or exclusion has been performed with various techniques, however, during the following years the left atrial appendage elimination often fails. We propose a novel, rapid surgery process of safely closing and obliterating the left atrial appendage by an intra‐atrial sutureless closure. Methods: The left atrial appendage elimination is performed by invaginating the appendage into the left atrium and tying it on the interluminal base to permanently prevent its evagination back into the normal position. Results: In the current study we present two cases where this technique was performed with a satisfactory result. In both cases the postoperative course was uneventful, and at follow‐up echocardiography the left atrial appendage was not visualized. Conclusions: While we have shown that this technique is feasible, a longer follow‐up and a larger series of patients is necessary before this method can be accepted in routine clinical practice.